SHIELDING PAKISTAN: THE IMPERATIVE STUDY OF R & D IN INFORMATION SECURITY FOR NATIONAL GROWTH AND STABILITY (Contemporary Journal of Social Science Review, 2025)
The increasing levels of computerization around the globe require an emphasis on information protection to counter between threats to economic, political, and social systems. With the growing importance of IT in every aspect of national security, economic growth, and technological prosperity for Pakistan, R & D has to be the key factor for improvement in digital power of any country. However, problems like lack of proper infrastructure, shortage of skilled workforce, and lack of integrated policies still remain the same, and the problem is even exacerbated by the use of technology in different industries. The systemic approach with collaboration of government, non-government organizations, private support, and technology and community awareness is mandatory. This research examines the impact of R &D in improving information security in Pakistan through Policy, Technology, Resources and Stakeholders by applying Partial Least Squares Structural Equation Modeling (PLS-SEM). Lack of Investment in R&D, Multiple Policies and Lack of PPP have been identified with Pakistan to be weak in combating cyber threats. According to the study’s findings, it is necessary to create specific research centers, support cybersecurity projects, start technical education, and update policies with international counterparts. Community engagement interventions are recommended to enhance the ability of the populace to protect their cyberspace resources. Thus, the mentioned gaps can be filled to strengthen the information security measures in Pakistan and set a course for development in the Fourth Industrial Revolution economy.